Jeho a její pohled: Střídavá péče z perspektivy matek a otců - Marta Vohlídalová (Gender a Výzkum)
The number of children in shared custody has been growing slowly in the CR. Today shared custody presents about 8 % of divorce cases with dependent children decided by courts. Despite this trend, there is a lack of research on how shared custody is practiced and experienced by Czech parents. The aim of this paper is to partially fill this gap. In the paper I ask how shared custody is related to the disruption of traditional gender ideology and performance of paternal and maternal roles and gender inequalities between partners. The analysis is based on 13 in-depth interviews with couples (mothers and fathers separately) who have shared custody. The analysis indicated that even if shared custody may be considered to be a tool for disrupting gender stereotypes and gender inequality between parents, it proved to be associated both with the confirmation and disruption of gender stereotypes associated with fatherhood and motherhood. While certain aspects of the practices and culture of shared custody are associated with “undoing gender”(especially regarding fatherhood), in other aspects it enhances and reproduces the gender power inequality between ex-partners and traditional expectations associated with parental roles.